PENINGKATAN HASIL BELAJAR MATEMATIK SISWA SMP DENGAN MENGGUNAKAN MEDIA ALAT PERAGA - Nurjanah, Siti Mariam; Setiawan, Wahyu; Sariningsih, Ratna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
With the help of teaching aids, this study intends to show how mathematics learning outcomes among students have improved. The sub-material used in this study is about slices and combinations. The venn diagram board is the teaching aid used in this research. This type of research is a Classroom Action Research (CAR) which was conducted in one of the junior high schools in Purwakarta Regency by involving 20 students of class VII as research subjects. The data collection technique used in this research is using a written test (daily test) in the form of a description of 8 items. Processing of data from the results of the written test in this study is using the percentage formula. Based on the data analysis of students' mathematics learning outcomes, namely a) In the first cycle there were 6 students (30%) who completed and 14 students (70%) did not complete, b) In the second cycle there were 12 students (60%) who completed and 8 students (40%) which are not completed. So based on the results of the analysis obtained from this study, it can be seen that learning by using teaching aids media can improve student learning outcomes.